The complete guide to landscape construction : 60 step-by-step projects for creating a perfect landscape. (Creative Pub. International, 2006)
"Includes projects ranging from basic earthmoving and yard shaping to creating privacy fences, pathways and watercourses. Features the latest in tools, techniques, products and materials, including vinyl fencing, tumbled retaining wall block and outdoor fireplaces"--Provided by publisher.